(untitled) (The Pakistan Development Review, 2007)
Global oil prices have shown an almost steady rise since 2003, with the April 2006 price double than that was in January 2004 [Bacon (2005)]. Demand, supply and speculative factors, and their interrelationships all leads to the steady rise in oil prices. In the last couple of years, global demand for oil grew due to economic strengthening in the US, as well as strong economic performance in developing Asia, (especially PR China and India). From 1990 to 2003 world demand for oil grew at the rate of 1.3 percent while for the People Republic of China and India (combined) at 7 percent rate and accounted for almost 40 percent of the demand growth1 [ADB (2005)].